2009
DOI: 10.1111/j.1365-2265.2008.03310.x
|View full text |Cite
|
Sign up to set email alerts
|

Eugonadal male patients with adrenal incidentalomas and subclinical hypercortisolism have increased rate of vertebral fractures

Abstract: SummaryObjective Subclinical hypercortisolism (SH) is suggested to exert a deleterious effect on bone. This effect and the role of gonadal status in male subjects are not fully elucidated. We evaluated bone mineral density (BMD) and prevalence of vertebral fractures in eugonadal male subjects with adrenal incidentalomas (AI) and without SH. Design This 12-month observational multicentre study was performed between January and December 2006 on inpatient basis in three referral Italian centres. Patients Eighty-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 32 publications
3
52
0
1
Order By: Relevance
“…This is in keeping with the concept that in glucocorticoid-induced osteoporosis, the fracture risk is partially independent of BMD. Indeed, as discussed earlier, in SH þ patients, the vertebral fracture prevalence is increased regardless of BMD, (12,13) suggesting that, similar to what occurs in the condition of overt cortisol excess, other factors, such as bone quality, also are involved in increasing the risk of fracture in SH.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This is in keeping with the concept that in glucocorticoid-induced osteoporosis, the fracture risk is partially independent of BMD. Indeed, as discussed earlier, in SH þ patients, the vertebral fracture prevalence is increased regardless of BMD, (12,13) suggesting that, similar to what occurs in the condition of overt cortisol excess, other factors, such as bone quality, also are involved in increasing the risk of fracture in SH.…”
Section: Discussionmentioning
confidence: 71%
“…(22) Subsequently, in two different cross-sectional studies, we found that in AI patients, SH was associated with an increased prevalence of vertebral fractures and that this association was independent of BMD, age, gender, and gonadal status. (12,13) However, to the best of our knowledge, no data regarding the incidence of vertebral fractures in SH are available so far. In this longitudinal study, we found an overall incidence of vertebral fractures of about 22%, which was higher in SH þ patients (48%) than in SH -subjects (13%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(13,14) The decrease in bone microarchitecture explains why in SHþ patients the fracture threshold is lower than in subjects without SH and why in 47% of SHþ patients fractures occur in spite of normal or only ''osteopenic'' BMD (Table 2), as shown in previous studies. (12,13) This is the first study specifically designed to assess the possible routine use of TBS in SHþ patients for detecting subjects at risk for fractures. Up to now, the techniques directly assessing Low TBS and low BMD were defined on the basis of the cutoffs with the best compromise between SN and SP obtained by ROC analysis (see Statistical Analysis Section) and set at À1.5 for TBS and 0.0 for BMD (both expressed as Z-scores).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that SH patients are at higher risk of complications of overt hypercortisolism, (2,3) such as osteoporosis (4)(5)(6)(7)(8)(9)(10) and vertebral fractures. (11)(12)(13)(14) Interestingly, some previous data has shown that in SH, as in overt hypercortisolism, the risk of fractures is scarcely predicted by bone mineral density (BMD), because fractures occurred in more than 40% of these patients despite a normal or only ''osteopenic'' BMD. (13,14) Thus, it has been hypothesized that in SH, as in overt hypercortisolism, not only bone mass but also bone quality (defined as microarchitectural deterioration of bone tissue) may be reduced.…”
Section: Introductionmentioning
confidence: 99%